PENGGUNAAN BAHASA DALAM GAME ONLINE MOBILE LEGENDS SERTA DAMPAK YANG DITIMBULKAN TERHADAP KESANTUNAN BERBAHASA REMAJA PADA USIA 16-25 TAHUN DI DESA INDRAPURA KAB.BATU BARA - Adelia Syafitri; Lisa Septia Dewi Br Ginting (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of technology and the internet has brought significant changes to the culture of Indonesian society, especially in the preservation of traditional media to new technology. One phenomenon that has emerged is the increasing use of online games, especially Mobile Legends: Bang Bang, which has become popular among teenagers. This research aims to analyze the use of language in these games, which tends to be informal and often contains slang and jargon, as well as the negative impacts of gaming addiction. Communication between players is an important factor, although it is often translated into harsh language and provocation, which can trigger conflict. In addition, Online Game Addiction can change teenagers' lifestyles, disrupting their way of thinking and behavior. This research is based on the author's experience in playing Mobile Legends, which makes it easier to collect data and understand the impacts.